Implementasi Manajemen Strategis Dalam Organisasi Non Profit (ONP) - Mustajib; Zaenul Fitri, Agus (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
This article discusses the implementation of strategic management in non-profit organizations, focusing on the independence of organizational financing, while the object of research at the fathul 'ulum kwagean islamic boarding school. With research questions on how to implement strategic management of financing and sources of financing in fathul 'ulum huts, the research method uses a descriptive qualitative approach, with the following results: At the beginning of the fiscal year all operational institutions under BUMP and pesantren must make RAP (Revenue Plan Plan) and RAB (Budget Plan), the supervision system is carried out by the administrative and financial districts. the sources of financing for pesantren come from BUMP (Pesantren-Owned Enterprises) with its subsidiaries; Ats-Tsuroyya Cooperative and Mini Market, TAS ( Savings for Santri Children) Kwagean, Kwagean Printing, Kwagean Screen Printing, Barokah Business, Hasbuna Rental, FC Shop. Shahara, Aquagean refillable gallons.